Integration of Theological and Sociological Values from Transcendental Phenomenological Perspective: Study of the Construction of Religious Moderation - Yakin, Ainul; Umiarso, Umiarso (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2024)
The existence of Islamic boarding school students is considered to have an essential role in guarding religious moderation amidst the increasing issues of radicalism and religious extremism in Indonesia. This research aims to understand the construction and implications of religious moderation based on theological and sociological values developed at the Miftahul Ulum Suren Islamic Boarding School, Jember, and the Nurul Jadid Paiton Islamic Boarding School, Probolinggo. This research method is qualitative with a case study approach. Data collection techniques are carried out through interviews, observation, and documentation. The results of the research show that the construction of religious moderation at the Miftahul Ulum Suren Jember Islamic Boarding School and the Nurul Jadid Paiton Probolinggo Islamic Boarding School, is carried out through the instillation of theological and sociological values, namely the aqidah ahlus sunnah wal jamaah and the habit of good morals towards Allah and others. The internalization of these theological and sociological values has implications for the character of students who love their country and have national and national awareness, as evidenced by an attitude of tolerance between religious communities, maintaining harmony and national unity